Sugarcane Borer, Diatraea saccharalis (Fabricius) (Insecta: Lepidoptera: Pyralidae) - John L. Capinera (EDIS)
The sugarcane borer, Diatraea saccharalis (Fabricius), is native to the western hemisphere, but not to the United States. It apparently was introduced into Louisiana about 1855, and has since spread to the other Gulf Coast States. It inhabits only the warmer portions of these states, however. Sugarcane borer also occurs throughout the Caribbean, Central America, and the warmer portions of South America south to northern Argentina. This document is EENY-217, one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: July 2001.